Penerapan Genset Sebagai Catu Daya Back Up Di Gedung Jatsc (Jakarta Air Traffic Service Center) - Riza Muhamad Zidan; Lela Nurpulaela (Jurnal Ilmiah Wahana Pendidikan, 2023)
The increasing dependency on electricity supply in important buildings, including air traffic service centres, has driven the need for a reliable backup system to maintain operational continuity. The JATSC (Jakarta Air Traffic Service Center) building as one of the important air traffic service centers in Jakarta, Indonesia, also faces similar challenges. In this study, an evaluation was made of the implementation of generators as a backup source of electricity in the JATSC Building. The main goal is to ensure a stable and continuous supply of electricity in the building, especially during emergency blackouts. An analysis of the power requirements and operational conditions of the JATSC Building was carried out, and an efficient backup system was designed. Implementation of generators as a backup source of electricity in the JATSC Building will provide significant benefits in maintaining operational continuity and reducing the risk of air traffic service disruptions. However, it is important to pay attention to the factors of reliability, regular maintenance and good supervision to ensure optimal performance of this backup system.